The impact of CEO duality attributes on earnings management in the East - Qaiser Rafique, Yasser; Abdullah, Al Mamun (Emerald Group Publishing Limited, 2015)
Purpose – This study aims to examine an important, yet understudied, relationship between board leadership structure and earning management. With conflicting theoretical and empirical evidence underpinning the debate the practice has fluctuated, investor perception of board leadership structure has altered, international regulation has reacted, scholarly conceptualizations of duality have become overly complex and the need to understand duality and conclude the debate has increased. Design/methodology/approach – This study examines the relationship between board leadership structure, firm financial performance and financial reporting quality of Australian, Malaysian and Pakistani publicly listed companies by using a sample of three years from 2011 to 2013. Findings – Results based on data collected from Australia, Malaysia and Pakistan indicate that the board leadership structure is not associated with firm performance and financial reporting quality. However, the female chief executive impacts negatively on firm performance in Malaysia and Pakistan. Further analyses reveal that the firm size is negatively related, while the grown firms in Australia having strong financial reporting quality. Research limitations/implications – The study is based on Australian Stock Exchange-20, Kuala Lumpur Stock Exchange-30 and Karachi Stock Exchange-30 companies from 2011 to 2013; however, a large sample from other emerging economies is required. Practical implications – The paper provides empirical evidence that unitary or dual leadership structure has no impact on public listed companies and would be of interest to regulatory bodies, business practitioners and academic researchers. Originality/value – This paper contributes to the literature on corporate governance and firm performance by introducing a framework for identifying and analyzing moderating variables that affect the relationship between board leadership structure and firm financial reporting quality.